Undergraduate Student Satisfaction with International Mobility Experiences - Elías, Silvina (2020)
Student mobility has recently become one of the most visible aspects of the internationalization of higher education institutions. A novel way of analyzing this strategy is to survey participant satisfaction. Student perception and satisfaction of was analyzed for two departments at the Universidad Nacional del Sur in Argentina. The methodological design was based on a survey and personal interviews. The survey questionnaire was created via GForms from Google Drive with four sections close-ended, single choice, multiple choice and Likert scale questions. The first section is aimed at obtaining personal and socioeconomic data from the students. The second section addresses the reasons that led students to participate in a mobility program; the third consists of assessment questions regarding how well the mobility program was organized and the fourth section addresses the degree of student satisfaction about the experience. The results reveal a high level of overall satisfaction among the students in both departments regarding their mobility experience. Although the possibility of participating in a mobility experience seems to be available to everyone, its feasibility, from a socio-economic point of view, remains elitist. A study abroad program during a student´s undergraduate degree has multiple benefits for both academic training and student personal development, arising from a coherence between their motivation compared to the final assessment of their experience. The resulting recommendations will be used to help obtain full recognition of courses taken at the host university.